Issues and Opportunities in the Development of Open and Distance Learning across Socio-Economic Development Sectors of Zambia - Musonda, Mutale M.; Shumba, Overson (West African Journal of Open and Flexible Learning, 2013)
This paper examines opportunities and challenges in the development of open and distance learning across socio-economic sectors within the context of Zambia’s Vision 2030. First, higher education institutions must partner with others to expand ODL opportunities for people in local communities. Second, issues undermining the effective adoption of ODL technologies and approaches must be interrogated and resolved. The issues include the low value ascribed to ODL approaches and ODL-attained competencies. This suggests the need to see ODL processes through a political lens to resolve the question: Who makes choices of ODL technologies, the content and their transactions? This leads to the proposition of the adoption and advancement of a transformative paradigm that enables ODL practitioners and users to see, interrogate and address questions of power and inequalities.